Subjective Well-Being Profile of Students at SMA Negeri 9 Bandung - Rizki, Tanzilal Wanda (Academia Edu Cendekia Indonesia (AEDUCIA), 2022)
Adolescence is a period that is quite vulnerable to change and challenges so adolescents need subjective well-being in their lives concerning true happiness and life satisfaction because if adolescents have high subjective well-being, they also show a higher level of success in the academic, social, and academic fields. intrapersonal. Hence, this study aims to describe the subjective well-being profile of students at SMA Negeri 9 Bandung. The research approach was carried out using a quantitative and descriptive method with a total of 305 students in class XI. From the students' subjective well-being instruments that have been distributed, several findings were obtained, namely the overall subjective well-being profile of students in the medium category with a percentage of 68% and the level of the tendency of students' subjective well-being in each dimension in the medium category.